A flamethrower mounted on UAV for kite litter clearing on high voltage transmission line - Angela Widiya Pratama; Fauzan Al Haqqi; Nur Anisa Sati’at; Yohandri Yohandri (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
The high voltage transmission line (HVTL) is a part of the electric power transmission system that distributes high-capacity electricity. There were numerous interruptions to the transmission line, one of which was caused by the kite getting stuck in the conductor. In the past, interference from kites on the conductor wire has been removed by crawling over it. This conventional method poses safety risks, is high-cost, and is time-consuming. This article describes the development of a flamethrower mounted on an unmanned aerial vehicle (UAV) for kite litter clearing on a high-voltage transmission line is presented. The flamethrower is fitted on the UAV to achieve high-mounted wire. The UAV was controlled using a transmitter and a receiver based on an Arduino. The flamethrower was tested for clearing a kite on the transmission line. The effect of nozzle diameter on flame burst length and the time it takes to burn a kite has been investigated. According to the experiment results, the performance of the flamethrower is highly satisfactory. Based on the component prices and manufacturing costs, the flamethrower has been successfully assembled at a low cost for a total of below $55.